Scientometric Analysis of the International Journal of Pharmaceutical Investigation Reflected as Publish or Perish - Mueen Ahmed, KK; Yunus, Mohammed; Chaman Sab, M (Information Research Communications, 2025)
Objectives The present study provides a scientometric evaluation of the International Journal of Pharmaceutical Investigation (IJPI) for the period 2011 to 2025, using data extracted through the Publish or Perish software based on Google Scholar records. Materials and Methods The analysis aims to assess Publication growth, citation performance, authorship patterns, institutional productivity, and international collaboration. Results A total of 971 documents were published during the study period, showing a steady annual growth rate of 7.66%. The journal achieved an average of 11.64 citations per paper, indicating moderate scholarly influence. Authorship analysis revealed 3,059 contributing authors with an average of 4.07 co-authors per paper, reflecting a strong culture of collaborative research. India emerged of 4.07 co-authors per paper, reflecting a strong culture of collaborative research. India emerged as the most productive country with 391 publications and 7,677 citations, followed by Iran, Malaysia, and Saudi Arabia. Dr. A.P.J. Abdhul Kalam Technical University and Jamia Hamdard were identified as the most prolific and impactful institutions. The VOSviewer visualisations revealed multi-cluster collaboration networks among authors, organisations, and countries. Conclusion The study concludes that IJPI has evolved into a dynamic and steadily growing journal, contributing significantly to pharmaceutical research through sustained publication activity, collaboration and academic visibility.
Keywords: Citation Impact; International Pharmaceutical Investigation; Pharmaceutical research; Publish of Perish; Research Collaboration; Scientometric Analysis.